Keabsahan Transaksi Jual Beli Secara Online Dalam Perspektif Hukum Islam: Studi Kasus Kurir Online Sangatta - Wahyuni, Serly; Aslamiah, Suaibatul; Kahar, Kahar (CV. Lentera Literasi Indonesia, 2025)
Research aimed was to determine whether the implementation of online buying and selling transactions implemented by Sangatta online couriers is in accordance with Islamic perspectives. Research method is a qualitative approach by a descriptive case study. Case studies are qualitative research that seeks to find meaning, investigate processes and gain insight and deep understanding of individuals, groups or situations. Data collection was conducted by interviewing the members of Sangatta online couriers as informants in this research. In addition, interviews were also conducted by several consumers. The research results are online buying and selling based on an Islamic perspective conducted by Sangatta online couriers on customers does not influence several online courier members to do so. However, Sangatta online couriers have implemented online buying and selling transactions in accordance by the Islamic law and produced results in the form of consumer satisfaction, so that consumers who have transacted through online couriers feel comfortable, satisfied and loyalty arises in transactions.